Methods for Protection of Key in Private Key Cryptography (International Journal of Innovative Research in Computer Science & Technology, 2024)
The susceptible nature of information against  forthcoming threats has become a ponderous affair for the  professionals of this field. It is a result of the rational and  steady struggle by the carrying people that has produced  multiple approaches which shields vital information from  speculated security attacks. For the everyday users who are  unfamiliar of these potential incursion(s) to their intimate  information, feel helpless when they encounter persecutor(s)  who wish to exploit the confidentiality of this elemental  information. Here we have discussed about a distinctive  approach which deal with these upcoming attacks. We have  tried to produce an algorithm which will safeguard users  against objectionable invasion of reserved information. We  have incorporated a set of diverse techniques to produce an  algorithm which is immune to these incursions. These  methods interpolate perceptions like Hybrid cryptography  [3], R.S.A. algorithm [1], Key management, Hash functions or  Encrypted key exchange.
Keywords: Hybrid cryptography; Security threats; Private Key cryptography; Public key cryptography; Cryptography; Encryption; Key; R.S.A; algorithm